Acarid Suction Cup‐Inspired Rapid and Tunable Magnetic Adhesion. Issue 8 (17th May 2021) - Hu, Xiaocheng; Fu, Yimou; Liu, Yide; Liu, Binhong; Qu, Shaoxing
Abstract: Adhesion appears in nature as a kind of clinging strategy for living creatures to survive in a complex environment. Nevertheless, the artificial counterpart applications are limited by many factors, such as slow responding rate and high driving voltage. In this paper, a novel magnetic adhesion achieved by the actuation of Ecoflex embedded with iron particles is presented, which is demonstrated by a magnetic suction cup (MSC) that can switch the adhesion state within 500 ms. Compared with suction cups made of the dielectric elastomer in existing literature, the present work's driving voltage is safe for humans. Furthermore, a mechanical model is developed and verified to optimize the design of the MSCs. By applying an altering magnetic field, the adhesive force varying with time exhibits complex waveforms such as sinusoidal wave, triangle wave, square wave, and even pulse wave can be achieved. For some situations that large adhesion force is not necessarily considered while the adhesion requires to be accurately and quickly controlled, such as transfer printing and intelligent sensing, the magnetic adhesion demonstrated in this article will enrich the future available applications. Abstract : This paper develops a rapid and tunable magnetic adhesion strategy inspired by acarid suction cup. In the text, a magnetic suction cup is demonstrated and the adhesion state of which can be adjusted by the pressure difference between the inside and outside of the suction cup. This adhesion strategy will open up applications in intelligent drive and sensing, transfer technology.